The Long-Term Outcome in a Cohort of 52 Patients With Symptomatic Intramedullary Spinal Cavernous Hemangioma After Microsurgery and Emergency Rescue Surgery - Duan, Yu; Mao, Renling; Qin, Xuanfeng; Liao, Yujun; Li, Jian; Chen, Gong (Frontiers in medicine, 2022)
Surgery is the mainstay treatment for patients with symptomatic intramedullary spinal cavernous hemangioma (ISCH), however the time of surgical intervention remains controversial. In this study, we proposed emergency rescue surgery (ERS) for patients in deteriorative type. The prognostic factors of patients with ISCH after microsurgery and the clinical effect of ERS were analyzed. From January 2013 to November 2019, 52 patients with symptomatic ISCH treated by microsurgical treatment were collected, ranging in age from 17 to 66 years old (mean: 45.8 ± 13.5 years). The course of the disease ranged from 2 days to 20 years. Of 52 lesions, 17 lesions were in the cervical segment, 25 in the thoracic segment, and 10 in the lumbosacral segment; while seven cases were at the ventral surface, 25 cases at the dorsal surface, and 20 cases at the central spinal cord. The sagittal diameter ranged from 1 to 58 mm (median: 17.3 mm). The transverse diameter ratio ranged from 20 to 80% (median: 50.7%). Thirty-two patients were diagnosed as deteriorative type and 22 were treated by ERS. At 12 months after surgery, all patients were followed up, and no residual or recurrence was found in all patients. Twenty-five patients (48.1%) showed spinal cord functional improvement after surgery; 25 (48.1%) had no functional change; 2 (3.8%) got worse. For deteriorative patients, ERS group had a significantly higher improvement rate than the non-ERS group (χ = 5.393, = 0.02); For all 52 patients, the factors as a lesion at the ventral surface (Z = 10.453, = 0.015), or lumbosacral segment (χ = 9.259, = 0.010) and longer course of disease (Z = -2.021, = 0.043) were potential risks in functional recovery in univariate analysis; and in multiple-factor analysis, the lesion at the lumbosacral segment (OR = 4.004, 95% CI: 1.341~11.961, = 0.013) was the independent risk factors for the functional recovery. Microsurgical resection is safe and effective for symptomatic ISCH. The ERS is an effective way to improve deteriorative patients' spinal cord function at long-term follow-up. The lesion at the lumbosacral segment is one of the poor prognostic factors.